St. Lucia : Staff Report for the 2002 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2003)
This 2002 Article IV Consultation highlights that after growing by an average 3 percent a year in 1998-99, output for St. Lucia stagnated in 2000, and fell by an estimated 5u percent in 2001. This reflected a severe drought in 2001, as well as lower tourism activity owing to the global economic slowdown and terrorist attacks of September 2001. In 2002, no growth is expected as tourism was weak, and tropical storm damage prevented a stronger recovery in banana production.